Kontribusi Bank Sampah Terhadap Pengurangan Dan Pengumpulan Sampah - Jodi Kurniawan; Rian Vebrianto (Universitas Lambung Mangkurat, 2020)
This activity aims to determine : the magnetude of the influence of waste banks on the healthand cleanliness of the community’s environment. The method of activity used is the location survey. From the results of the activity, it can be seen that the final waste disposal site is 14.6 million tons/year, compost is 2.2 million tons/year, 1.8 million tons/year is burned, and enviromental watr dumped is around 1.6 million tons/year. So it can be concluded that the contribution of the garbage bank can be developed is worth reducing waste in Indonesia.